A novel quasi-oppositional harmony search algorithm and fuzzy logic controller for frequency stabilization of an isolated hybrid power system. (March 2015) - Tarkeshwar,; Mukherjee, V.
Highlights: Modeling of an IHDG with SMES to supply electricity to the end user is carried out. The tunable model parameters are tuned by a novel QOHS algorithm. FLC's membership functions and rule bases are optimized by this algorithm. For on-line, real-time application, a fuzzy logic controller is designed. Controller is tested for system uncertainties, stochastic load variation and wind speed. Abstract: The intermittent wind power in isolated hybrid distributed generation (IHDG) may cause serious problems associated with frequency ( f ) and power ( P ) fluctuation. Energy storage devices such as battery, super capacitor, and superconducting magnetic energy storage (SMES) may be used to reduce these fluctuations associated with f and P . This paper presents a study of IHDG power system for improving both f and P deviation profiles with the help of SMES. The studied IHDG power system is consisted of wind turbine generator and diesel engine generator. Both f and P control problems of the studied power system model are addressed in presence or absence of SMES. Fuzzy logic based proportional–integral–derivative (PID) controller with SMES is used for the purpose of minimization of f and P deviations. The different tunable parameters of the PID controller and those of the SMES are tuned by a novel quasi-oppositional harmony search algorithm. Performance study of the IHDG power system model is carried out under different perturbation conditions. The results demonstrate minimum f and P deviations may be achieved by using the proposed fuzzy logic based PID controller along with SMES.